Antibiofilm activity of 3,3'-diindolylmethane on Staphylococcus aureus and its disinfection on common food-contact surfaces - Hui Zhang; Xiaomei Guo; Lei Tian; Na Wang; Yuqing Li; Ariel Kushmaro; Robert Marks; Qun Sun (Food Science and Human Wellness)
This study explored the antibiofilm efficacy of 3,3'-diindolylmethane (DIM) on Staphylococcus aureus and its disinfection on common food-contact surfaces. The minimum biofilm inhibitory concentration (MBIC) of DIM on S. aureus was 62.5 μmol/L, while it did not impede the bacterial growth evaluated by growth curve and XTT reduction assay. DIM in the concentration range of 31.2−62.5 μmol/L demonstrated a dose-dependent antibiofilm activity to S. aureus, as confirmed by light microscopic (LM), confocal laser scanning microscopic (CLSM), and scanning electron microscopic (SEM) analyses. At DIM of 62.5 μmol/L, the biomass of S. aureus biofilm was significantly reduced by 97 % and its average thickness by 58 % (P < 0.05). DIM of 62.5 μmol/L inhibited the bacterial initial adhesion and proliferation, as well as cell motility; the release of extracellular DNA (eDNA) and extracellular polysaccharide (EPS) were reduced by 75 % and 69 %, respectively. DIM exhibited a strong inhibition to S. aureus biofilm formation on common food-contact surfaces, including 304 stainless steel, glass, and polyvinyl chloride (PVC) but not disperse the mature biofilm. Overall, our investigation identified DIM as a promising antibiofilm agent and its suitability to prevent the biofilm formation of S. aureus on common food-contact surfaces utilized during food processing.